Optimizing juz 30 memorization through traditional qur’anic methods: Tasmi’ and muroja’ah at baitul huda - Wahda Zulfa Inayatuz Zahra; Luluk Ifadah; Faizah; Mohamad Ardin Suwandi (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research aims to find out the implementation of tasmi' and murojaah methods to accelerate hafalan al quran jul 30 on the centri. The method in this research is qualitative with a phenomenological approach. Data collection techniques use observations, interviews, and documentation. Data is analyzed interactively using the Miles & Huberman model of data collection, data reduction, data presentation, and conclusion drawings. The results of the research show: 1) The application of the methods of tasmi’ and muraja’ah is done by memorizing gradually and repeating readings in order. Tasmi’ method is carried out in a group with reading tartil, focusing on memorizing, memorizing, and justifying reading errors, while muroja’a is done with repetition of reading 41 times or for 15-20 minutes; 2) the application factor of methods tasmi ‘and muraja'ah is motivation center, family support is structured and there is a goal of hafalan, while the inhibitor is less consistent, making it difficult to regulate the time and methods of monotonous teaching; 3) attempts to cope with hafalan with a regular schedule in groups, establish communication with the student’s guardian, and add new learning methods.